Targeted [compact disc, unabridged] a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel (Brilliance Audio (Firm)), 2022)
Bob Lee Swagger's congressional hearing is cut short when the committee and himself are taken hostage by a group of violent operatives. The very people who had accused him must depend on him to get them out alive.